Greta Thunberg’s Life-Writing on Facebook: A Quantitative Analysis - Oleksandr Kapranov (Acta Universitatis Wratislaviensis. Anglica Wratislaviensia)
Greta Thunberg is an iconic figure, whose engagement in the issues of the environment and climate change has made her a household name (Molder et al. 668). Another factor that contributes to her recognizability by millions of people globally involves her active online presence on social networking sites (SNSs), which she utilizes to communicate her views on climate changeand environment-related issues (Bergmann and Ossewaarde 267). The article presents a quantitative study on Greta Thunberg’s status updates on Facebook, which are problematized as instances of life-writing in digital personhood, which involves an online diary afforded by SNSs in general and Facebook in particular (Ortiz-Vilarelle 9). The study aimed at collecting a corpus of Thunberg’s Facebook status updates and analysing them quantitatively in order to establish frequently recurring lexical patterns, which shed light onto her preferred ways of construing climate change- and environment-related discourse. The corpus analysis, which was executed in the software program AntConc, revealed that Thunberg’s life-writing on Facebook was characterized by such frequently occurring lexical items, as self-mentions (e.g., we) and the words climate and strike. The findings were further discussed in detail in the article.